Application of Internet of Things Technology in Monitoring Water Quality in Fishponds - Putra , Fauzan Prasetyo Eka; Ubaidi, Ubaidi; Saputra, Rama Nurja; Haris, Farras Maulana; Barokah, Selviana Nur Rizqi (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Monitoring water quality in fish ponds is essential to maintain fish health and productivity. In recent years, Internet of Things (IoT) technology has emerged as an effective solution to efficiently monitor and manage water quality. This article describes the application of IoT technology in monitoring the water quality of aquaculture ponds with the aim of improving fish productivity and welfare. Data on water quality parameters such as temperature, dissolved oxygen, pH, ammonia levels, and turbidity can be monitored in real time through a network of connected sensors. The main advantage of using IoT for fish pond water quality monitoring is that it can provide accurate and fast information on water conditions. This allows fish farmers to proactively take appropriate actions to maintain an optimal water environment for fish growth. In addition, integration with data management and remote monitoring systems allows fish pond owners to continuously monitor water conditions, even in remote locations. This helps reduce the risk of environmental damage and fish loss due to inappropriate water quality conditions. Therefore, the use of IoT technology for water quality monitoring in fish ponds not only increases productivity but also ensures the well-being of fish and reduces negative impacts on the environment.